POLILATERAL GASTRODIPLOMACY: MENGUNGKAP INTERAKSI ANTAR AKTOR DALAM AKTIFITAS GASTRODIPLOMASI INDONESIA DI LOS ANGELES - Indra Kusumawardhana; Bhardanshah Mohammad (Universitas Nasional, 2018)
The international relations study has experienced a lot of movement in the dinamic, looking at patterns in an increasingly of the dynamic of dipomacy, then it is considered to give the influence into the development of the science of international relations. This paper deals with how the theory or concept of Polilateral Gastrodiplomacy describes the movement patterns of diploamcy. The authors trying to see the interactions between actors in diplomacy, especially in an effort to develop Indonesia's culinary business in Los Angeles. Interactions between these actors and then encourage the presence of a development that can be mutually beneficial but depending on the aspect of what being a concentration. The authors also assume that the interaction that is formed into a new style in running the diplomatic mission of Indonesia.